2017
DOI: 10.1002/slct.201700889
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalysed Tandem Synthesis of Substituted Quinazolines from Phenacyl Azides and O -Carbonyl Anilines

Abstract: An efficient protocol for the synthesis of substituted quinazolines from 2-aminoacetophenones/benzophenones and phenacyl azides using copper catalysed base mediated system is developed. This method utilizes phenacyl azides for generation of imine precursors for transimination with o-carbonyl anilines followed by condensation to yield quinazolines. This mild catalytic system is efficient in construction of two CÀN bonds in a single operation. The reaction proceeded well to give a series of 22 examples of quinaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The method involved the transimination of o -aminoketones 8 with in situ -generated imine, obtained from the decomposition of phenacyl azides 88, in the presence of Cu(OAc) 2 in Et 3 N as the base and acetonitrile as the solvent, at room temperature for 45 min, enabling the formation of substituted quinazolines 89 in 60%–85% yields ( Scheme 12C ). ( Sastry et al, 2017 ) The reaction proceeded smoothly with a wide range of substituents on the aromatic ring. However, alkyl acyl azide instead of 88 failed to form the desired product.…”
Section: First-row Transition Metal Catalystsmentioning
confidence: 93%
See 3 more Smart Citations
“…The method involved the transimination of o -aminoketones 8 with in situ -generated imine, obtained from the decomposition of phenacyl azides 88, in the presence of Cu(OAc) 2 in Et 3 N as the base and acetonitrile as the solvent, at room temperature for 45 min, enabling the formation of substituted quinazolines 89 in 60%–85% yields ( Scheme 12C ). ( Sastry et al, 2017 ) The reaction proceeded smoothly with a wide range of substituents on the aromatic ring. However, alkyl acyl azide instead of 88 failed to form the desired product.…”
Section: First-row Transition Metal Catalystsmentioning
confidence: 93%
“…Commercially available starting materials and a wide substrate scope make this strategy advantageous. The reaction proceeds through the Fe-mediated Frontiers in Chemistry frontiersin.org 10 Gopalaiah et al (2017) reported for the first time the formation of 2-aryl/heteroaryl quinazolines 34 in 61%-94% yields from 2aminobenzyl alcohols 20 and benzylamines 33 in the presence of FeBr 2 in chlorobenzene at 110 °C under aerobic oxidation for 24 h (Scheme 4C) (Gopalaiah et al, 2017).…”
Section: Ironmentioning
confidence: 99%
See 2 more Smart Citations
“…On account of this method, a library of 2-arylquinazoline derivatives can be easily prepared in good isolated yields. Recently, in the same line, Kamal et al employed 2-aminobenzophenones 28 and phenacyl azides 71 for the construction of quinazolines 72 by using cupric acetate, triethylamines in acetonitrile at ambient temperature (Visweswara Sastry et al, 2017 ). This procedure proceeded well and constructed two C–N bonds in a single operation ( Scheme 22C ).…”
Section: Transition Metal-catalyzed Methodologiesmentioning
confidence: 99%